1978
DOI: 10.1042/bj1750221
|View full text |Cite
|
Sign up to set email alerts
|

Modification of yeast ribosomal proteins. Methylation

Abstract: Two-dimensional polyacrylamide-gel electrophoretic analysis of yeast ribosomal proteins uniformly labelled in vivo with [methyl-3H]methionine and [1-14C]methionine revealed that four ribosomal proteins are methylated, i.e. proteins S31, S32, L15 and L41. Lysine and arginine appear to be the predominant acceptors of the methyl groups. The degree of methylation ranges from 0.09 to 0.20 methyl group per modified ribosomal protein species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 21 publications
4
26
0
1
Order By: Relevance
“…YL1 (L3) was detected only by Cannon et al [ 5 ] . In the small subunit, Kruiswijk et al [7] detected, as we found, protein YS28 (S32) as the most significantly methylated. On the other hand, Hernandez et al of YS5 (S4).…”
Section: Identification Of the Ribosomal Proteins Methylated In Vivosupporting
confidence: 51%
See 3 more Smart Citations
“…YL1 (L3) was detected only by Cannon et al [ 5 ] . In the small subunit, Kruiswijk et al [7] detected, as we found, protein YS28 (S32) as the most significantly methylated. On the other hand, Hernandez et al of YS5 (S4).…”
Section: Identification Of the Ribosomal Proteins Methylated In Vivosupporting
confidence: 51%
“…Taking into account the fact that half of the protein radioactivity was in basic amino acids, we can estimate that the large subunit contains about 10 methyl groups in protein while the small contains only a few (2 -4), This estimation is much higher than that of Kruiswijk el a]. [7], who used a double-labelling method and estimated, indirectly, that the large and small subunits contained 0.29 and 0.25 methyl group respectively.…”
Section: Results a N D Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…There are currently 137 established ribosomal protein genes in Saccharomyces cerevisiae, which encode 79 unique ribosomal proteins (46 large subunit and 33 small subunit) (8). The physical and biochemical characterization of yeast ribosomes has been complicated not only by the large number of proteins involved, and their highly basic amino acid content, but also by the presence of modifications, often in combination, including N-terminal processing and acetylation (9), methylation (21,22), and phosphorylation (23,24).…”
mentioning
confidence: 99%